Climate-based Management to Reduce Nitrate Leaching from Dairies in the Suwannee River Basin - Victor E. Cabrera; Norman E. Breuer; Peter E. Hildebrand; Clyde Fraisse (EDIS)
Dairy farmers in the Suwannee River Basin are aware that environmental issues will be among the greatest challenges they face in the near future. Dairy waste is thought to be an important factor contributing to nitrogen pollution in local waters. Dairy farmers are now required to comply with stricter environmental regulations, either under permit or under voluntary incentive-based programs. Dairies face increased regulation because of social pressure, while larger herds attract the attention of neighbors and activists concerned with odors, flies, and especially, potential leaching of nutrients that might influence water quality (Giesy et al., 2003). his document is IFAS Circular 1464, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Sciences, University of Florida. Published January 2005.